THE INFLUENCE OF PROFIT SHARING RATE AND FINANCING RISK ON CUSTOMER INVESTMENT INTEREST IN INDONESIAN SHARIA BANKS WITH CUSTOMER TRUST AS A MODERATING VARIABLE IN PALOPO CITY - Hilal; Asri Sakina; Amnang; Ahmad Efendi; Nadila; Hamida (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the effect of profit sharing rates and financing risks on customer investment interest at Bank Syariah Indonesia (BSI), with customer trust as a moderating variable. This study uses a quantitative approach with a survey method through the distribution of questionnaires to Bank Syariah Indonesia customers. The data analysis technique used is Structural Equation Modeling–Partial Least Squares (SEM-PLS) using the SmartPLS 4 application. The results show that the profit sharing rate has a positive and significant effect on customer investment interest. This indicates that the higher and more competitive the profit sharing rate offered, the higher the public's interest in investing in Islamic banking products. Financing risk does not significantly affect customer investment interest because most people still have a high level of trust in the ability of Islamic banks to manage financing and maintain financial stability. In addition, customer trust has been shown to have a positive and significant effect on customer investment interest. However, customer trust is unable to moderate the relationship between the profit sharing rate and financing risk on customer investment interest. This study shows that the main factors influencing customer investment interest at Bank Syariah Indonesia are the profit sharing rate and customer trust. Therefore, Islamic banks need to improve transparency, service quality, and maintain the stability of their profit-sharing systems to sustainably increase public investment interest.